2020
DOI: 10.3390/cells9040850
|View full text |Cite
|
Sign up to set email alerts
|

TRPCs: Influential Mediators in Skeletal Muscle

Abstract: Ca 2+ itself or Ca 2+ -dependent signaling pathways play fundamental roles in various cellular processes from cell growth to death. The most representative example can be found in skeletal muscle cells where a well-timed and adequate supply of Ca 2+ is required for coordinated Ca 2+ -dependent skeletal muscle functions, such as the interactions of contractile proteins during contraction. Intracellular Ca 2+ movements between the cytosol and sarcoplasmic reticulum (SR) are strictly regulated to maintain the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 198 publications
(230 reference statements)
0
24
0
Order By: Relevance
“…The presence of SOCE in skeletal muscle was first identified in 2001 122 . There are several differences between SOCE in skeletal muscle cells and general SOCE in another cell types [5][6][7] . First, the SR or t-tubule in skeletal muscle corresponds to the ER or plasma membrane, respectively.…”
Section: A Reverse-directional Signal From Casq1 To Socementioning
confidence: 99%
See 1 more Smart Citation
“…The presence of SOCE in skeletal muscle was first identified in 2001 122 . There are several differences between SOCE in skeletal muscle cells and general SOCE in another cell types [5][6][7] . First, the SR or t-tubule in skeletal muscle corresponds to the ER or plasma membrane, respectively.…”
Section: A Reverse-directional Signal From Casq1 To Socementioning
confidence: 99%
“…Cytosolic [Ca 2+ ] at rest (nM range) rises to the μM range during skeletal muscle contraction 4 . To establish the Ca 2+ increase, in addition to the Ca 2+ from the SR, extracellular Ca 2+ entry via Ca 2+ channels in the t-tubule membrane, such as Orai1 or transient receptor potential canonical type (TRPC), also participates in the cytosolic Ca 2+ increase, especially for skeletal muscle contraction during tetanic stimulation or fatigue [5][6][7] . The relaxation of skeletal muscle involves the reuptake of Ca 2+ from the cytosol to the SR to reset the resting cytosolic Ca 2+ level and replenish SR Ca 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…ATP-driven Ca 2+ pumps pump out Ca 2+ from the cytoplasm, including the sarcoplasmic reticulum (SR) Ca 2+ ATPase that pumps it back into the SR and the plasma membrane Ca 2+ -ATPase ( Brini and Carafoli, 2009 ) that pumps it out of the cytoplasm into the extracellular space. Furthermore [Ca 2+ ] i is also regulated by Ca 2+ influx through TRPC channels ( Choi et al, 2020 ), store-operated Ca 2+ channels ( Lyfenko and Dirksen, 2008 ), the bidirectional and electrogenic Na + /Ca 2+ exchanger in the plasma membrane ( Cifuentes et al, 2000 ; Fraysse et al, 2001 ; Blaustein, 2013 ) and by passive leak from the SR through the ryanodine receptor ( Yang et al, 2007 ; Eltit et al, 2010 ; Andersson et al, 2011 ; Lamboley et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently suggested that SACs might undergo functional inactivation during unloading, possibly contributing to atrophy establishment [ 218 ]. Among SACs, the stretch-activated and Ca 2+ permeable TRPC1 channel is expressed in skeletal muscle and interacts with α-1-syntrophin PDZ domain and caveolin-3 [ 219 , 220 , 221 , 222 , 223 ]. This channel has been found to be responsible for anomalous extracellular Ca 2+ entry in dystrophic muscle fibers [ 220 , 222 , 223 ].…”
Section: Master Regulators Of Muscle Atrophymentioning
confidence: 99%
“…Among SACs, the stretch-activated and Ca 2+ permeable TRPC1 channel is expressed in skeletal muscle and interacts with α-1-syntrophin PDZ domain and caveolin-3 [ 219 , 220 , 221 , 222 , 223 ]. This channel has been found to be responsible for anomalous extracellular Ca 2+ entry in dystrophic muscle fibers [ 220 , 222 , 223 ]. Downregulation of TRPC1 in adult mouse muscles induces atrophy per se, pointing to a relevant role of this channel in muscle mass regulation [ 224 ].…”
Section: Master Regulators Of Muscle Atrophymentioning
confidence: 99%